The dominant three-element model of oil and gas accumulation in basement buried hills: A discussion on new exploration frontiers in the deepwater area of the northern South China Sea - Gongcheng Zhang; Chengfu Lyu; Dongsheng Yang; Shuai Guo; Long Wang (Journal of Natural Gas Geoscience, 2024)
Basement buried hill reservoirs represent significant emerging prospects among the newly discovered growth poles in the deepwater areas of the northern South China Sea. Addressing the unclear key factors contributing to their formation, this study dissects successful global exploration cases of basement buried hill reservoirs and analyzes the common characteristics of basement reservoir accumulation under different basin types, structural backgrounds, basement lithologies, and oil and gas geological conditions. A three-element coupling relationship, termed “source-reservoir-cap”, is proposed as the dominant mechanism controlling basement buried hill reservoir formation. The genesis of these reservoirs requires adequate oil and gas supply, appropriately sized accumulation bodies, and effective sealing layers. The optimal configuration of the “source-reservoir-cap” relationship directly influences the efficient charging and preservation of oil and gas within basement buried hill reservoirs. Four configurations are identified, including circumstances such as the source-underlying low-positioned basement buried hill with a “source-reservoir cover docking migration type”, the source-border middle-positioned basement buried hill with a “source-reservoir lateral window docking migration type”, and the source-outside high-positioned basement buried hill with both “source-reservoir short-distance transport and migration type” and “source-reservoir long-distance transport and migration type”. The first to three models present favorable accumulation conditions. Based on the “source-reservoir-cap” three-element coupled model, this study identifies the Yunkai basement buried hill in the Pearl River Mouth Basin, the central depression in the Qiongdongnan Basin, and the northern and southern basement buried hills belts as crucial exploration targets in the deepwater areas of the northern South China Sea.